The Effect of Weblog Use on Improving Summary Writing Skill - Khataibeh, Almazah (Jordan Journal of Educational Sciences, 2019)
This study aimed at investigating the effect of expository weblog on improving summery writing skill for first secondary grade female students’ in Hakama secondary school in Irbid, Jordan. The researcher prepared a weblog with educational content about the summary writing skill, to train the members of the study on the summary writing skill. She also prepared a list that includes skills (function indicators) relating to summary writing. The researcher developed a test to measure the performance of the students in summary writing skill. The test consisted of (6) paragraphs from the contents of the books for students of the First Secondary Grade, except for the book of the Arabic language intended for training through weblog. The researcher also developed a criterion for the evaluation of performance in the test. The study sample consisted of (82) female Students, who are divided into two classes, for the academic year (2017/2018) and the school was chosen upon convenience. The quasi-experimental approach was adopted through two groups: The experimental group consisted of (42) students who studied the reading texts in Weblog manner, and the second was a control group consisting of (40) students who studied the texts as usual. The two groups were chosen randomly, and the study took (8) weeks. The results show a statistically significant differences between the averages of the performance of members of the study sample in each skill of the summary writing skills in favor of the experimental group